2009
DOI: 10.7863/jum.2009.28.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of 3-Dimensional Ultrasonography of the Kidney Using an In Vitro Renal Model

Abstract: Three-dimensional ultrasonography proved to be more accurate than 2DUS for intrarenal measurements using this in vitro renal model. Three-dimensional ultrasonography has the potential to ease diagnostic renal scanning with the ability to further scrutinize and postprocess the scanned volumes. The model was realistic in its anthropomorphic properties and simulated human tissue during puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the pioneer study in [23], the authors determined the feasibility and accuracy of 3D US reconstruction of the pelvicaliceal system (PCS) in an in vitro porcine kidney. A further study in [24] has demonstrated that 3D US is more accurate than 2D US for PCS measurements on a customized phantom. The authors in [24] then performed 3D US-guided punctures on that phantom and proved the feasibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pioneer study in [23], the authors determined the feasibility and accuracy of 3D US reconstruction of the pelvicaliceal system (PCS) in an in vitro porcine kidney. A further study in [24] has demonstrated that 3D US is more accurate than 2D US for PCS measurements on a customized phantom. The authors in [24] then performed 3D US-guided punctures on that phantom and proved the feasibility.…”
Section: Resultsmentioning
confidence: 99%
“…A further study in [24] has demonstrated that 3D US is more accurate than 2D US for PCS measurements on a customized phantom. The authors in [24] then performed 3D US-guided punctures on that phantom and proved the feasibility. Therefore, it is a nature idea that the accuracy and repeatability would be improved further by intruding a 3D US system into our guidance framework.…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin-based phantoms have been described for developing ultrasound-guided biopsy technique [3,4], but these do not facilitate the complex procedural sequence required to insert a drain into a dilated pelvicalyceal system. A gelatin-based system has recently been described that allows ultrasound-guided puncture of a simulated pelvicalyceal system [5], but the costs and complexity of production may be prohibitive for routine use by trainees. We therefore describe a cheap and relatively simple technique, adapted from previously described methodology [3,4], for producing a gelatinbased phantom that permits ultrasound-guided puncture, wire insertion, serial dilatation and drainage of a fluid-filled cavity that simulates the dilated collecting system of a hydronephrotic kidney.…”
mentioning
confidence: 99%